STUDI STUDI KASUS: ANALISIS PROSEDUR PEMERIKSAAN MR IMAGING ORBITA DENGAN MEDIA KONTRAS PADA KASUS RETINOBLASTOMA - hernastiti sedya utami; Fani Susanto; Redha Okta Silfina (Medical Imaging and Radiation Protection Research Journal, 2022)
Diagnosis of orbital is recommended for orbital MRI examinations, on of the pathology is retinoblastoma. orbital organs contain a lot of soft tissues so the orbital MRI is one of the right choices because it can appear anatomically and pathologically in a cross-sectional orbital, in two dimensions and three dimensions. Examination protocols on orbital MRI in retinoblastoma cases have several sequences in pre- and post-contrast agent. The purposes of this research were to determine the orbits MRI procedure in the retinoblastoma case. The Method of this research is a descriptive of qualitative with case study method. The data were collected in unit of radiology DR. Saiful Anwar Malang by using observation method, documentation, and interview of radiolog and radiographers. Data analyzed by using presented and data reduction to get the conclusion and suggestion. The results are an orbital MRI examination is concerned with MRI safety with patient screening and informed consent. The protocol for pre-contrast agent orbital MRI was T1 3D TSE axial, T2 TSE axial, DWI axial, T2 TSE fat saturated axial, and T2 DRIVE axial. On post-contrast agent using sagittal T1 FFE sequences, T1 3D TSE axial. The use of slice thickness is 3mm and 1mm in 3D image, 2D T2 DRIVE and 2D T1 FFE post contrast. gadolinium contrast agent as much as 5 mmol/10ml injection intravenously. The selection of sequences in the protocol of orbital MRI can produce detailed orbital anatomy images and provide sufficient clinical information to diagnose retinoblastoma.